Spatial Distribution Patterns of Lantana camara L. Population as Invasive Alien Species In Pringtali Savana Bandealit Resort Meru Betiri National Park - Sulistiyowati, Hari; Rahmawati, Emitria; Wimbaningrum, Retno (Jurnal ILMU DASAR, 2021)
Bandealit is one of the resorts in Meru Betiri National Park (MBNP). This area has many endemic floras and faunas affected by the presence of invasive alien spesies plants. These plants tend to give negative impacts on savana ecosystem among them is, Lantana camara L. The distribution of this invasive alien spesies in the savana can be used to provide information about the characteristic of the environment. This study was conducted to investigate the patterns of spatial distribution of invasive alien L. camara population in the Pringtali Resort Bandealit savana region. The characters of plant species morphology was recorded for species name identification and validation. Percent cover of the individual L. camara species was collected within 50 plots (5x5 m2), while each of coordinate species found in the plots was recorded by using GPS (Global Positioning System). Abiotic factors such as temperature, pH, light intensity, and soil moisture were measured within the plots. The location of the data collection is 5,000 m2. The distribution pattern of invasive alien L. camara population was analyzed using ArcGIS and Dispersion Morisita’s Index (Ip). The result showed that 51.7% of L. camara population grew spasially close together (clumped) or overlapped one another based on the ArcGIS. This means that L. camara individuals distributein clumped pattern. While the other individuals (48.3%) grew apart randomly from each other. This distribution pattern showed by Ip value, 0.51 was also clumped or clustered. It can be concluded that the distribution pattern ofinvasive alien species L. camara is clumped because the reproduction of plant was by seeds dispersal or vegetative buds that lived around parental individuals.Keywords: ArcGIS, Lantana camara L., Invasive Foreign Plants, Morisita index, Distribution Pattern.